2021
DOI: 10.1016/s2468-2667(20)30292-9
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic position and use of hospital-based care towards the end of life: a mediation analysis using the English Longitudinal Study of Ageing

Abstract: Background Many patients prefer to avoid hospital-based care towards the end of life, yet hospitalisation is common and more likely for people with low socioeconomic position. The reasons underlying this socioeconomic inequality are not well understood. This study investigated health, service access, and social support as potential mediating pathways between socioeconomic position and receipt of hospital-based care towards the end of life. Methods For this observational cohort study, we included deceased parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 25 publications
(39 reference statements)
3
25
1
Order By: Relevance
“…GHTD between URRBMI and UEBMI beneficiaries during the study period. A recently published study reported socioeconomic factors were associated with inequalities in EOL care utilization [33]. As shown in our data, the demographic and socioeconomic factors were different between URRBMI and UEBMI beneficiaries, but the association of HI schemes with GHTD attenuated and remained significant after adjusted relevant factors, suggesting that the difference in the proportion of GHTD between URRBMI and UEBMI beneficiaries might be partially explained by differences in demographic and socioeconomic factors.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…GHTD between URRBMI and UEBMI beneficiaries during the study period. A recently published study reported socioeconomic factors were associated with inequalities in EOL care utilization [33]. As shown in our data, the demographic and socioeconomic factors were different between URRBMI and UEBMI beneficiaries, but the association of HI schemes with GHTD attenuated and remained significant after adjusted relevant factors, suggesting that the difference in the proportion of GHTD between URRBMI and UEBMI beneficiaries might be partially explained by differences in demographic and socioeconomic factors.…”
Section: Discussionsupporting
confidence: 61%
“…A recently published study reported socioeconomic factors were associated with inequalities in EOL care utilization. 33 As shown in our data, the demographic and socioeconomic factors were different between URRBMI and UEBMI beneficiaries, but the association of HI schemes with GHTD attenuated and remained significant after adjusted relevant factors, suggesting that the difference in the proportion of GHTD between URRBMI and UEBMI beneficiaries might be partially explained by differences in demographic and socioeconomic factors. For URRBMI beneficiaries, who are already at a socioeconomic disadvantage compared with their UEBMI counterparts, less comprehensive service coverage and lack of financial protections might further aggravate the inequalities in EOL care utilization.…”
Section: Discussionsupporting
confidence: 54%
“…This is because of the diversity in individual patients’ preferences for dying at home [ 34 ], challenging the assumption that all deaths in hospital indicate poor access to care. More recent evidence suggests that increasing use of hospital services at the end of life by people in a more disadvantaged socioeconomic position is partly explained by poor health [ 14 ], suggesting reasons beyond access to care may influence the likelihood of dying in hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Most research on socioeconomic inequities in accessing palliative and end-of-life care examines differences in receipt of care, often indicating an association between socioeconomic disadvantage and a lower likelihood of receiving specialist palliative care [ 10 13 ]. Conversely, use of hospital-based care in the last year of life tends to be higher for those in a more disadvantaged socioeconomic position, with poorer health likely accounting for some of this use [ 8 , 14 , 15 ]. However, receipt of care is only one component to accessing care.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst other previous studies revealed similar patterns [ 23 ], others showed an inverse relationship between socioeconomic status and healthcare expenditures at end-of-life [ 24 ]. The findings are understandable considering that individuals belonging to lower socioeconomic commonly report worse health and functioning, which can lead to more frequent use of hospitalization services at end-of-life [ 25 ]. As no financial barriers exist to access services under the English National Health Service (NHS), differences in costs may be a reflection of poorer management rather than financial barriers [ 24 ].…”
Section: Discussionmentioning
confidence: 99%